Effectiveness of the KOTAKU (City Without Slums) Program in Sidoarjo Regency - Widodo, Anton; Riyadh UB, Ahmad (Indonesian Journal Publisher, 2024)
This study aims to assess the effectiveness of the KOTAKU program in reducing slum settlements in Sruni Village, Gedangan Sub-district, Sidoarjo Regency. It will also examine the factors that support and hinder its success. This research takes a qualitative approach. Milles and Hubberman's qualitative analysis was utilized to explore the data. According to the study's findings, the KOTAKU Program has been effective because it fits the indications of clear objectives to be met, straightforward strategies for reaching program objectives, and a sound process of analysis and policy creation; the KOTAKU program has been successful because it meets the indicators of clear program objectives, straightforward strategies for achieving program objectives, a solid policy analysis and formulation process, careful planning, appropriate program preparation, availability of work facilities and infrastructure, effective and efficient implementation, and an educational monitoring and control system. There are both supportive and hindering aspects to the KOTAKU program. Facilitator competency, proper facilities, a sufficient budget, and a clear organizational structure are beneficial. The restricting elements are inaccurate information or hoaxes about the KOTAKU Program that circulate on social media and a restricted number of facilitators that assist with program implementation.